Comparison of the Effectiveness of Storytelling Therapy and Cognitive-Behavioral Play Therapy in Improving Cognitive Emotion Regulation in Children with Attention-Deficit/Hyperactivity Disorder - Torabinia, Elham; Bahrami Hidaji, Maryam; Kraskian Mujemnari, Adis (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to determine and compare the effects of storytelling therapy and cognitive-behavioral play therapy on improving cognitive emotion regulation in children with attention-deficit/hyperactivity disorder. In terms of variable control, the present study was quasi-experimental and was conducted using an extended pretest–posttest–follow-up design with a control group. The statistical population included all children aged 7–10 years with attention-deficit/hyperactivity disorder in the city of Jam during 2025–2027. A total of 36 participants were selected through purposive sampling and were randomly and equally assigned to two experimental groups and one control group. The experimental groups separately received the interventions, consisting of eight 60-minute sessions, while the control group received no intervention. Data were collected using the SNAP test and the Cognitive Emotion Regulation Questionnaire developed by Garnefski et al. (children’s version). The data were analyzed using two-way analysis of variance with repeated measures on one factor, also known as mixed-design analysis of variance, and Bonferroni post hoc tests. The results showed that both interventions led to a significant improvement in cognitive emotion regulation, including adaptive and maladaptive cognitive emotion regulation strategies, and that there was no significant difference between the two interventions. Moreover, the intervention effects remained stable at the follow-up stage. The findings emphasize the necessity of using play-based and narrative-based interventions as complementary interventions in the treatment of children with attention-deficit/hyperactivity disorder.